The Omega-3 Polyunsaturated Fatty Acid DHA Induces Simultaneous Apoptosis and Autophagy via Mitochondrial ROS-Mediated Akt-mTOR Signaling in Prostate Cancer Cells Expressing Mutant p53. (10th June 2013) - Shin, Soyeon; Jing, Kaipeng; Jeong, Soyeon; Kim, Nayeong; Song, Kyoung-Sub; Heo, Jun-Young; Park, Ji-Hoon; Seo, Kang-Sik; Han, Jeongsu; Park, Jong-Il; Kweon, Gi-Ryang; Park, Seung-Kiel; et al.
Abstract : Docosahexaenoic acid (DHA) induces autophagy-associated apoptotic cell death in wild-type p53 cancer cells via regulation of p53. The present study investigated the effects of DHA on PC3 and DU145 prostate cancer cell lines harboring mutant p53. Results show that, in addition to apoptosis, DHA increased the expression levels of lipidated form LC3B and potently stimulated the autophagic flux, suggesting that DHA induces both autophagy and apoptosis in cancer cells expressing mutant p53. DHA led to the generation of mitochondrial reactive oxygen species (ROS), as shown by the mitochondrial ROS-specific probe mitoSOX. Similarly, pretreatment with the antioxidant N-acetyl-cysteine (NAC) markedly inhibited both the autophagy and the apoptosis triggered by DHA, indicating that mitochondrial ROS mediate the cytotoxicity of DHA in mutant p53 cells. Further, DHA reduced the levels of phospho-Akt and phospho-mTOR in a concentration-dependent manner, while NAC almost completely blocked that effect. Collectively, these findings present a novel mechanism of ROS-regulated apoptosis and autophagy that involves Akt-mTOR signaling in prostate cancer cells with mutant p53 exposed to DHA.